Analisis Yuridis Pekerja Tetap Yang Melakukan Pemutusan Hubungan Kerja Karena Pengunduran Diri - Marito, Eugina Evita (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Indonesia began to recognize and has established since after independence the protection of various workers' rights in employment relationships as outlined in statutory regulations. Permanent Workers mark the establishment of an employment relationship based on the existence of an Indefinite Time Work Agreement (PKWTT) as the implementation of employment regulations related to a fixed period or nature. An employment agreement can end due to the termination of the employment relationship between two parties, namely the employee and the employer, unilaterally by the employee, one of which is for reasons of resignation, which is increasingly vulnerable to occurring. The normative juridical method used in this research refers to and is based on norms and regulations in statutory regulations, as well as other research on legal systematics related to termination of employment (PHK), providing research results that even though the time is continuous, permanent workers have the right. to end the employment relationship by submitting a resignation because it is one of the reasons for layoffs permitted by law since the Employment Law until now the Job Creation (Ciptaker) Law. Workers and the company must pay attention to the obligations carried out by each party as well as the rights that will be obtained as a result of resignation. This obligation takes the form of a procedure for submitting a resignation request using the procedures regulated in Article 81 point 42 of the Ciptaker Law. Meanwhile, workers also receive their rights in the form of compensation money and separation pay as an obligation from the company as stated in Article 81 number 44 of the Job Creation Law and also Article 50 PP No. 35 of 2021 concerning Specific Time Work Agreements, Outsourcing, Working Time and Rest Time, and Termination of Employment Relations.